2017
DOI: 10.1364/oe.25.022017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal chiral events in a semiconductor laser with coherent injection

Abstract: We study experimentally and theoretically the dynamics of a spatially extended (along the propagation direction) oscillatory medium with coherent forcing. We observe abnormally high events, responsible for a different statistics of intensity and pulse height, in a regime where solitons and roll patterns are unstable. We focus on the formation of these high-peak events and their connection to the phase dynamics. Each abnormal event can be associated with a change in the slope of the phase time trace. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Consequently during a roundtrip time the phase evolves as a positive kink from 0 to 2π. Further studies have shown that phase solitons display long range interaction and can form complexes with multiple chiral charge [13] or give rise to complex dynamics and extreme or abnormal events [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently during a roundtrip time the phase evolves as a positive kink from 0 to 2π. Further studies have shown that phase solitons display long range interaction and can form complexes with multiple chiral charge [13] or give rise to complex dynamics and extreme or abnormal events [14,15].…”
Section: Introductionmentioning
confidence: 99%